Silent Serial Sensations : The Wharton Brothers and the Magic of Early Cinema - Lupack, Barbara Tepa (Book collections on Project MUSE., 2020)
"Filmmakers Ted and Leo Wharton, whose serials became popular in the 1910s, established a model for incremental storytelling and holdover suspense still employed by filmmakers and television producers more than a century later"--